2009
DOI: 10.1016/j.compscitech.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, duration and speed of pre-mixing on the dispersion of clay/epoxy nanocomposites

Abstract: The effect of temperature, duration and speed of pre-mixing on the dispersion of organoclay in epoxy was studied. The technique of high-speed mixing process was used. Epoxy and Cloisite 30B were pre-mixed at different temperatures, different speeds and for different durations of time. The quality of dispersion and intercalation/exfoliation of organoclay in epoxy after pre-mixing (before adding hardener) was analyzed by means of X-ray diffraction (XRD) and viscosity measurement. The dispersion and intercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…In order to achieve the desired properties of epoxy-clay nanocomposites, it is important to understand the role of the surface modifier and how the interfacial interaction occurs. Besides that, mixing parameters such as mixing speed, mixing duration, and temperature do play an important role in the formation of the final structure/configuration (conventional, intercalated, or exfoliated) of epoxy-clay nanocomposites [18].In recent years, utilizing a bi-functionalized nanoclay in preparation of PNCs is gaining more interest from the research community. Shakeri et al [19] reported on a modification of organoclay with 3-trimethoxysilylpropyl methacrylate (MPS) as a reactive silane coupling agent to prepare a polymethylmethacrylate (PMMA)/OMMT nanocomposite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve the desired properties of epoxy-clay nanocomposites, it is important to understand the role of the surface modifier and how the interfacial interaction occurs. Besides that, mixing parameters such as mixing speed, mixing duration, and temperature do play an important role in the formation of the final structure/configuration (conventional, intercalated, or exfoliated) of epoxy-clay nanocomposites [18].In recent years, utilizing a bi-functionalized nanoclay in preparation of PNCs is gaining more interest from the research community. Shakeri et al [19] reported on a modification of organoclay with 3-trimethoxysilylpropyl methacrylate (MPS) as a reactive silane coupling agent to prepare a polymethylmethacrylate (PMMA)/OMMT nanocomposite.…”
mentioning
confidence: 99%
“…In order to achieve the desired properties of epoxy-clay nanocomposites, it is important to understand the role of the surface modifier and how the interfacial interaction occurs. Besides that, mixing parameters such as mixing speed, mixing duration, and temperature do play an important role in the formation of the final structure/configuration (conventional, intercalated, or exfoliated) of epoxy-clay nanocomposites [18].…”
mentioning
confidence: 99%
“…and chemical (chemical structure and reactivity of the components, affinity, etc.) nature [10][11][12][13][14]. Since the surfaces of virgin layered silicates are hydrophilic, significant hindrances appear at synthesis of high-performance polymer/clay nanocomposites comprising hydrophobic polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…how well the dispersion of clay is in epoxies. Recently, Ngo et al have studied the effect of temperature, duration and speed of pre-mixing on the dispersion of Cloisite 30B clay in DGEBA epoxy [115]. Their findings show that pre-mixing at higher speed and temperatures improved the intercalation/exfoliation of clay during cure.…”
Section: Clay/epoxy Nanocompositesmentioning
confidence: 99%
“…For POSS-MMT, the POSS-imidazolium cations were incorporated into clay using the cationic exchange procedure before mixing with the epoxy. The mixture was premixed under high-speed mechanical shear for an extended period to allow diffusion of epoxy molecules into the clay galleries [115]. The pre-mixing stage was monitored with POSS-imidazolium modified clay/epoxy systems POM at selected intervals and the consequential micrographs suggest marked improvement in dispersion with prolonged mixing time and the clay was broken down into smaller particles gradually (Fig.…”
Section: Morphological Studiesmentioning
confidence: 99%